To Re-Establish The Image Of Galogandang Pottery - Hendratno, Hendratno (2012)
The ceramics in Indonesia has many historical stories since the ancient times. Not only in Java as the main area of ceramic’s area, but also in Sumatera. Sumatera Island, especially in the West part of Sumatera also has the center of ceramics, and it is located in called Galogandang village. Galogandang village and its pottery become the major issue in this research. It shows not only about the Galogandang’s in brief, but how to the development of ceramics itself. Galogandang’s pottery as one of the livelihood sources of the community needs such improvement whether in technique, design and marketing process. By introducing the new technique, applying new design and improving the marketing process hopefully it will give a big contribution in the development of Galogandang’s pottery. The main goal of all these process is to create a good economic condition of Galogandang’s community without reducing the original culture or ‘adat’ value in the community.